Statistical properties of nonlinear wave signatures in OH and O2 airglow brightness data observed at lower midlatitudes - Scheer, Jurgen (2010)
Among 2187 nights of airglow observations of the OH(6-2) and O2b(0-1) bands from Argentina (mainly from El Leoncito, 32°S 69°W), 132 show airglow brightness jumps (ABJs) of short duration (16 min median). ABJs are supposed to be related to mesospheric bores or similar nonlinear waves. Several occurrence patterns were identified, which a successful explanation must take into account. ABJs occur preferably in the OH layer at 87 km, and are less likely in the O2 layer at 95 km, maybe because ducts prefer lower altitudes. The seasonal distribution of nights when ABJs are observed only in the OH layer clearly shows a winter maximum centered around solstice, and equinox minima. In contrast, the seasonal distribution of ABJ nights in O2 is flat. Most ABJs simultaneously present in OH and O2 show anticorrelated variation between both layers. ABJ nights tend to occur in clusters lasting several days, which probably reflects duct lifetime.